2020
DOI: 10.1210/clinem/dgaa555
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Thyroid Dysfunction During Pregnancy and the Risk of Adverse Outcomes in the Offspring: A Systematic Review and Meta-Analysis

Abstract: Context Previous studies suggested a potential link of maternal thyroid dysfunction with adverse neurocognitive outcomes and impaired development of internal organs in offspring. Objective To review the association between maternal thyroid dysfunction and the risk of adverse outcomes in offspring. Data Sources PubMed, EMBASE and Cochrane Library. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 62 publications
1
38
0
4
Order By: Relevance
“…Thyroid dysfunction is a common endocrine disorder in pregnant women, and consists of imbalanced thyroid hormone levels (including overt and subclinical hypothyroidism, overt and subclinical hyperthyroidism) and positive thyroid antibody status. Studies have shown that about 0.3%-3% of pregnant women suffer from hypothyroidism (1). Hypothyroidism leads to multiple adverse outcomes such as premature delivery, miscarriage, neurodevelopmental dysplasia, and increased risk of autism and asthma in the offspring (1)(2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thyroid dysfunction is a common endocrine disorder in pregnant women, and consists of imbalanced thyroid hormone levels (including overt and subclinical hypothyroidism, overt and subclinical hyperthyroidism) and positive thyroid antibody status. Studies have shown that about 0.3%-3% of pregnant women suffer from hypothyroidism (1). Hypothyroidism leads to multiple adverse outcomes such as premature delivery, miscarriage, neurodevelopmental dysplasia, and increased risk of autism and asthma in the offspring (1)(2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that about 0.3%-3% of pregnant women suffer from hypothyroidism (1). Hypothyroidism leads to multiple adverse outcomes such as premature delivery, miscarriage, neurodevelopmental dysplasia, and increased risk of autism and asthma in the offspring (1)(2)(3)(4)(5). In addition, more pregnant women (about 18%) are tested positive for thyroid autoantibodies (Thyroid peroxidase antibody, TPOAb or thyroglobulin antibody, TgAb), which will also adversely affect pregnant women and their offspring (1).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the number of studies that addressed the association between insufficient levels of maternal thyroid hormones and child brain development is considerable ( 1 , 17 ). A recent systematic review and meta-analysis identified nine observational studies on the association between maternal hyperthyroidism in pregnancy and neurodevelopmental diseases in the offspring including attention deficit hyperactivity disorder, autism spectrum disorder, epilepsy, and schizophrenia ( 35 ). Most of these studies were register-based studies, which are typically large, but are hampered by the fact that the assessment of exposure in pregnancy is indirectly performed from hospital diagnoses and/or redeemed prescriptions of drugs.…”
Section: The Hypothesis Of Fetal Programmingmentioning
confidence: 99%
“…Most of these studies were register-based studies, which are typically large, but are hampered by the fact that the assessment of exposure in pregnancy is indirectly performed from hospital diagnoses and/or redeemed prescriptions of drugs. For each of the different outcomes, only two individual studies were included in a meta-analysis, and the combined measures showed a significant association between maternal hyperthyroidism and ADHD and epilepsy in the child ( 35 ). In another study ( 36 ), using a case-cohort design, the assessment of maternal hyperthyroidism was made from the measurement of thyroid function parameters in stored blood samples from the early pregnancy.…”
Section: The Hypothesis Of Fetal Programmingmentioning
confidence: 99%
“…The prevalence of SCH during pregnancy has been increasing year by year, and it has become an important complication of pregnancy. Its adverse effects on pregnancy outcomes are becoming clear, including spontaneous abortion [1] , preeclampsia [2] , placental abruption, premature rupture of membranes, low birth weight [3] , fetal distress, preterm birth [4] , and abnormal neuropsychological and intellectual development [5] . The pathogenesis of SCH remains unclear and might be associated with nitric oxide (NO) [6] , Nesfatin-1 [7] , gene silencing mediated by microRNAs [8] , inactivation and mutation of the thyroid-stimulating hormone receptor gene [9] , and the gut-thyroid axis [10] .…”
Section: Read Full License Introductionmentioning
confidence: 99%